PENGEMBANGAN MEDIA COMPUTER ASSISTED INSTRUCTION (CAI) UNTUK PEMBELAJARAN MENGENAL ANGGOTA TUBUH ANAK USIA 4-5 TAHUN - Nurul Lutfiyati Afifah; Ningrum, Mallevi Agustin (Universitas Islam Raden Rahmat Malang, 2023)
This development research aims to produce a technology-based media product, namely the Computer Assisted Instruction (CAI) media that is feasible for learning to know body parts of children aged 4-5 years which is motivated by the limited media that is able to support learning to know body parts in online learning systems in early childhood education. So, it is necessary to develop a technology-based learning media that is able to support learning to know body parts in an effective, interactive, interesting and fun way in online learning systems in early childhood education. The method used in this research is R&D (Research and Development) using the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate). The test subjects in this study were material experts, media experts and 15 early childhood education teachers in Surabaya. This study uses questionnaires and interviews via google form as a data collection methods. The data analysis technique in this study used the Guttman measurement scale. The results of the CAI media validation carried out by material experts and media experts obtained results with